The Secret Behind Anemia in Patients With Acromegaly - Firlatan, Busra (J Endocr Soc, 2021)
Introduction: The GH/IGF-1 axis has regulatory effects on erythropoiesis. GH deficiency is associated with normocytic anemia in adults, and hemoglobin (Hb) concentrations are normalized after GH replacement. Little is known about the significance of anemia in acromegalic patients. The aim of this study is to evaluate the factors associated with anemia in patients with acromegaly. Methods: A single‐center retrospective cohort study was conducted. A total of 381 acromegalic patients who admitted to the University Hospital from 1980 to 2018 were included. Information regarding the demographic features, the pre-operative and follow-up hormone levels, radiological features of adenoma, treatment modalities, comorbidities, presence of cancer, colonoscopy results, medication history, presence and type of anemia together with the CBC, iron parameters, 25(OH)D, and vitamin B12 levels at the time of anemia detected were retrieved from the patient record system. Anemia was defined as Hb levels <12.0 g/dL in women and <13.0 g/dL in men. Results: Of 381 acromegalic patients (120F/98M, age: 44±13yr/45±12 yr); 218 cases (57.2%) were diagnosed with anemia (67% normocytic, 33% microcytic) at a median duration of 6 months after the diagnosis of acromegaly. Hb values were 11.1±0.9 g/dL in women and 12.1±1.0 g/dL in men. Serum levels of ferritin and transferrin saturation were lower in anemic patients (p<0.001). The levels of 25(OH)D and vitamin B12 were lower in the anemic group, but the differences were not statistically significant. Anemia was detected more likely in patients who had macroadenoma (p=0.001), suprasellar extension (p=0.001), and cavernous sinus invasion (p<0.001) on pre-op MRI and residue tumor (p<0.001) on post-op MRI. Patients with anemia had higher GH, IGF-1 and PRL levels (p<0.01), and there was a significant difference related to the use of octreotide (p<0.001). Anemia was observed more frequently in patients with a history of radiotherapy (29% vs. 10%, p<0.001). Hypopituitarism was seen in 63 (29%) patients in the anemic group and 21 (13%) patients in the non-anemic group (p<0.001). Cancer prevalence in the study population was 14.2%, and the most commonly diagnosed cancers were thyroid, bladder, prostate, and breast. Although not statistically significant, the prevalence of cancer was higher in anemic patients compared to non-anemic patients (17% vs. 10%). There was no significant difference regarding the presence of colorectal polyps between groups, and only two anemic patients were diagnosed with colon cancer. Conclusion: This is the first study highlighting that anemia is a common comorbidity in patients with acromegaly, and that anemia can be related to characteristics of the tumor, hormonal status, type of treatment, and the presence of cancer in addition to nutritional factors. Therefore, a comprehensive evaluation is required for anemia in acromegalic patients.